Vitality among university students: exploring the role of gratitude and resilience. Issue 3 (14th August 2020) - Garg, Naval; Sarkar, Ayatakshee
Abstract : Purpose: Vitality is an occurrence of having extremely high energy, stamina, physical or mental vigor. This study tends to investigate whether gratitude and resilience lead to vitality. In particular, it tends to examine the necessity and sufficiency of gratitude and resilience for vitality among Indian university students. Design/methodology/approach: The collected data are analyzed with the help of different statistical tools like the measure of central tendency, standard deviation, correlation, linear and multiple regression, and necessary condition analysis. Findings: The results establish both gratitude and resilience as sufficient and necessary conditions for the occurrence of vitality among students. Theoretical and practical implications, along with scope for future researchers, are also elaborated. Practical implications: Though universities are the active change agents and change-makers in the lives of the students, the onus of positive transformation lies on both students and the university administration. Hence these prosocial measures like gratitude and resilience, which are self-regulating, self-professed and competent, help to build internal psychological resources to promote sustainable vitality. Originality/value: The present study is probably the first study that explores sufficiency and necessity of resilience and gratitude for vitality among students. The findings suggest that university administration may rely on gratitude and resilience-based interventions to enhance vitality of students.